Burden of Cardiovascular Diseases in Nepal from 1990 to 2019: The Global Burden of Disease Study, 2019 - Achyut Raj Pandey; Meghnath Dhimal; Niraj Shrestha; Dikshya Sharma; Jasmine Maskey; Raja Ram Dhungana; Bihungum Bista; Krishna Kumar Aryal (Hindawi - Cambridge University Press, 2023)
Cardiovascular diseases (CVDs) have emerged as the leading cause of deaths worldwide in 2019. Globally, more than three-quarters of the total deaths due to CVDs occur in low- and middle-income countries like Nepal. Although increasing number of studies is available on the prevalence of CVDs, there is limited evidence presenting a complete picture on the burden of CVDs in Nepal. In this context, this study aims to provide comprehensive picture on the burden of CVDs in the country. This study is based on the Global Burden of Disease (GBD) study 2019, which is a multinational collaborative research covering 204 countries and territories across the world. The estimations made from the study are publicly available in the GBD Compare webpage operated by the Institute for Health Metrics and Evaluation (IHME), University of Washington. This article makes use of those data available on the GBD Compare page of IHME website to present the comprehensive picture of the burden of CVDs in Nepal. Overall, in 2019, there were an estimated 1,214,607 cases, 46,501 deaths, and 1,104,474 disability-adjusted life years (DALYs) due to CVDs in Nepal. The age-standardized mortality rates for CVDs witnessed a marginal reduction from 267.60 per 100,000 population in 1990 to 245.38 per 100,000 population in 2019. The proportion of deaths and DALYs attributable to CVDs increased from 9.77% to 24.04% and from 4.82% to 11.89%, respectively, between 1990 and 2019. Even though there are relatively stable rates of age-standardized prevalence, and mortality, the proportion of deaths and DALYs attributed to CVDs have risen sharply between 1990 and 2019. Besides implementing the preventive measures, the health system also needs to prepare itself for the delivery of long-term care of patients with CVDs which could have significant implications on resources and operations.